Effect of Company Size, Asset Growth, and Profitability Against the Capital Structure in Automotive Companies - FIRDIAN SARIFAH USMALIA; HALIAH; ANDI KUSUMAWATI; ERIKA PUTRI CANDRA LESTARI (International Journal of Multidisciplinary Research and Studies, 2023)
This study aims to determine the effect of company size, asset growth, and profitability variables on the capital structure of automotive companies on the Indonesia Stock Exchange for the 2016-2020 period. The sample in this study was 30 from 12 automotive companies listed on the Indonesia Stock Exchange and selected using purposive sampling. Linear regression analysis and significance tests are used to prove the hypothesis with the help of SPSS version 26. The research data used is data sourced from financial reports of automotive companies listed on the Indonesia Stock Exchange (BEI). The results of this study show that company size, asset growth, and profitability have no significant effect on capital structure.